Membaca ‘Kuasa’ Michel Foucault dalam Konteks ‘Kekuasaan’ di Indonesia - Kebung, Konrad (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2017)
This article presents Foucault’s ambitious thoughts on various historical events in the past and sees how people faced and reacted to all these events in different eras of thinking, ways of life, cultures and historical settings. He works with past events, yet his objective is to constitute a history of the present. His rich analyses in his works are classified in three main axes, namely the axis of knowledge, of power, and of ethics or subject. The author of this article also presents Foucault’s notion on power as practiced throughout the history of systems of thought, and how this way of thinking can be read into in any political power, or how Foucault’s thinking can be seen as a criticism on various repressive powers practiced everywhere, including in Indonesia.